Bench-scale composting of recycled paper mill sludge using chicken manure + duck manure, kitchen wastes and agricultural wastes as nitrogen amendments - Gallo, Jurex; Naraval, Jose Jr.; Gallardo, Susan (2011)
The study determined the effect of carbon to nitrogen ratio (C/N) and N amendments in bench-scale composting of recycled paper mill sludge. N amendments used in the study included mixed chicken manure + duck manure, kitchen wastes and agricultural wastes. Experiments were conducted in three bench-scale reactors designed to simulate a composting system. Mixed chicken manure + duck manure as N amendment was used to adjust the C/N of composting feedstock to 20:1 and 30:1. Test parameters included temperature, free air space (FAS), pathogens and nutrient content of compost products. Feedstock amended with mixed chicken manure + duck manure with initial C/N of 30 was favorable and results are in agreement with the findings of previous studies. Although the initial feedstock with C/N=20 had the highest reduction in volatile solids, it emitted foul odor due to ammonia emission all throughout the composting process. The total NPK in composts produced by manure-amended feedstocks passed the requirements of the Fertilizer and Pesticide Authority; however, pathogens present in compost exceeded the United States Environmental Protection Agency standards. Further investigations were also conducted using kitchen wastes and agricultural wastes as N amendments for composting recycled paper mill sludge at initial C/N of 30. Based on composting performances and quality of compost products, results of treatments using kitchen-waste-amended feedstock and agricultural-waste-amended feedstock were outweighed by the results of treatment using mixed chicken manure + duck manure as N amendment. High ammonia emission was observed in kitchen-waste-amended feedstock while the FAS of agricultural-waste-amended feedstock significantly dropped in the early stage of composting.
Keywords: Fertilizers and manures; Composting; Feed mills